Evaluating the Effectiveness of Kindergarten Programs for Children with Hearing Impairments (HIs) from the Point of View of Parents - Abu-Radwan, Ena’am Hassan (Dirasat: Educational Sciences, 2020)
This study aimed to detect the effectiveness level of kindergarten programs for children with hearing impairments (HIs) from parents’ the point of view.The study sample consisted of (43) parents.To achieve the study aims, the researcher developed a scale to evaluate the effectiveness of programs submitted to children with hearing impairment.The validity and reliability of the scale were calculated.The scale consisted of (96) items divided into 9 dimensions.The study results indicated that the level of the effectiveness of kindergarten programs for children with hearing impairments from the point of view of parents was high in all dimensions. The study also indicated that there were significant differences in the level of the effectiveness of kindergarten programs that can be attributed to educational degree variable in favor of the BA degree holders on methods and teaching aids dimentions.There were no significant differences attributed to the variable of economic level.The study recommended conducting another study to identify the extent of parents’ participation in programs provided for their children with hearing impairments.